Compact UWB BPF With Broad Stopband Based on Loaded-Stub and C-Shape SIDGS Resonators - Xie, Jiacheng; Tang, Deshan; Shu, Yiyang; Luo, Xun (IEEE microwave and wireless components letters, 2022)
In this letter, two types of substrate-integrated defected ground structure (SIDGS) resonators (i.e., loaded-stub and C-shape resonators) are proposed for the ultra-wideband (UWB) bandpass filter (BPF) design. Coupled SIDGS resonators can generate four transmission poles to achieve the UWB response with low insertion loss in a compact size. Besides, the spurious cancellation with a broad stopband is achieved by mutual suppression of separated harmonics from the SIDGS resonators. In addition, the lowpass units (LPUs) embedded in the microstrip feed-lines are utilized to further improve the BPF stopband rejection. To verify the mechanism, a compact BPF operating at 6.85 GHz (i.e., the passband center frequency f_{0} ) with 0.6-dB insertion loss and 3-dB fractional bandwidth (FBW) of 114% is implemented and fabricated. The measured stopband extends to 9.7f_{0} with a rejection level more than 26 dB.